Solo City Batik Design Security System (SiKemTi Solo) During the Pandemic Covid-19: Inggris - Kusanti, Jani; Sudalyo, Ramadhian Agus Triono (Politeknik Ganesha Medan, 2021)
Safeguarding copyright on traditional batik works is very important to prevent duplication of Indonesian cultural products. The ease of duplicating, especially in batik designs, causes frequent violations of the design's copyright. Especially with the rise of online commerce today, it is easier for everyone to use other people's products and copy other people's products. This will not happen if there is already a system that can be used to secure the design work. For this reason, it is important to develop methods that can be used to secure traditional batik works, especially Surakarta. Based on these problems, a research was conducted on the application of image watermarking techniques that are resistant to changes generated by image processing in the form of compression. The method used to secure Surakarta batik works is compression using wavelet transformation. The aim is to develop a batik design security system method using the watermarking method. The steps taken started with taking photos of batik designs and the designer's name, photos in the form of images followed by the embedding process using the watermarking method. The watermarking method used is the DWT method. After encryption, identification is carried out to determine the level of errors that occur. The results of testing 323 batik image data in this study obtained an average mse level = 0.00000065 and an average psnr result = 188.471186102179. From the results of this study, it was found that the development of methods that can be used to secure batik products by using the watermarking method.